Methodology for probabilistic tsunami-triggered oil spill fire hazard assessment based on Natech cascading disaster modeling - Nobuhito Mori (Reliability Engineering & System Safety, 2024)
A novel modeling methodology is presented for cascading disasters triggered by tsunami hazards considering uncertainties. The proposed methodology focuses on tsunami-triggered oil spills and subsequent fires, a type of natural hazard-triggered technological (Natech) event. The methodology numerically simulates the time-varying behavior of tsunami-triggered oil spill fires for numerous stochastically generated scenarios and performs a probabilistic mapping of the maximum radiative heat flux as a quantitative measure of the fire hazard. To enable these assessments, probabilistic tsunami hazard assessments are extended to include the tsunami-induced movement of oil storage tanks, resulting oil spills, tsunami-driven oil fire spread, and thermal radiation from fires. The uncertainty of the earthquake fault slip distribution, oil filling level of storage tanks, and fire starting time and position is incorporated into the new assessments. To demonstrate the methodology, a realistic case study is conducted for a coastal petrochemical industrial park in Japan conditioned on possible offshore moment magnitude 9.1 earthquakes. Contrary to typical tsunami direct impact assessments, the results highlight the cascading effects of tsunamis and large variability in key output variables concerning oil spills and fires. This indicates that the methodology is useful for deepening stakeholders’ understanding of tsunami-triggered cascading disasters and improving risk reduction plans.